2021
DOI: 10.1108/aaouj-08-2021-0097
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of undergraduate distance learners: a cross-sectional study

Abstract: PurposeMental health is as important as physical health and new university entrants report high prevalence of depression. In open and distance learning (ODL), students must manage both work and studies. Those who are unable to effectively balance these aspects may experience negative outcomes such as dropping out, distress and physical health problems. Therefore, the study aims to investigate psychological distress amongst distance-learning undergraduate students to gather evidence for recommending necessary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(72 reference statements)
0
3
1
Order By: Relevance
“…A study of medical students reported the reason for having higher stress among senior students might be due to the difficulty in making career choices, and opinions, and a lack of self-confidence in fitness for future clinical practice 69 . In contrast to the current findings, younger and distance learners in OUSL (e.g., Humanities and social sciences, Natural science, Engineering, Education and Health sciences faculties) had reported significantly higher levels of stress, anxiety, and depressive symptoms although they used 21-DASS scale like the current study 39 . However, only depressive symptoms had a significant impact by the academic year in the current study (p < 0.05).…”
Section: Prevalence Of Stress Anxiety and Depressive Symptomscontrasting
confidence: 99%
See 1 more Smart Citation
“…A study of medical students reported the reason for having higher stress among senior students might be due to the difficulty in making career choices, and opinions, and a lack of self-confidence in fitness for future clinical practice 69 . In contrast to the current findings, younger and distance learners in OUSL (e.g., Humanities and social sciences, Natural science, Engineering, Education and Health sciences faculties) had reported significantly higher levels of stress, anxiety, and depressive symptoms although they used 21-DASS scale like the current study 39 . However, only depressive symptoms had a significant impact by the academic year in the current study (p < 0.05).…”
Section: Prevalence Of Stress Anxiety and Depressive Symptomscontrasting
confidence: 99%
“…Unlike the Western literature, a few researchers in Sri Lanka have been studying psychological problems and coping strategies encountered by undergraduates studying in some state and non-state universities. The distance-learning undergraduates at the Open University of Sri Lanka experienced nearly 51% psychological distress due to the distance mode of education while having low levels of anxiety and depression 39 . Some studies have reported psychological illbeing among undergraduates due to the combat of Covid-19 40 .…”
mentioning
confidence: 99%
“…For example, in previous studies in Vietnam [53], [54], Pakistan [55], Malaysia [56], and China [57], students tend to have moderate to extremely severe DASS symptoms. When compared to other studies conducted in Malaysia [37], Indonesia [37], [57], Thailand [37], [58], and Sri Lanka [59] students have a much lower level of DASS. Using the Mann-Whitney U test, it can be concluded that the DASS symptomatology as presented in Table 5 in both the working student groups and students' status groups (i.e., regular and irregular) was not statistically significant.…”
Section: Resultsmentioning
confidence: 54%
“…The results of this study are in line with the results of research at universities in Bangladesh which states that mental health disorders include "psychological distress" relating to the anxiety levels they reported. At the same time, depression (35%) and stress remained (20%) (Gamage and Herath, 2021). Furthermore, mental health in categories No.…”
Section: Multivariate Analysis Of Demographic and Lifestyle Factors W...mentioning
confidence: 92%